PENGELOLAAN KURIKULUM SEKOLAH ALAM DARUL ISTIQAMAH MAROS - Sofyan, Ahmad; Fathur Rokhman; Asrori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine in depth the management of the natural school curriculum in improving the quality of education at Sekolah Alam Darul Istiqamah (SADIQ) Maros, South Sulawesi. The focus of the research is directed at the process of planning, organizing, implementing, and evaluating nature-based curriculum that is integrated with the Independent Curriculum and Islamic values. This study uses a qualitative approach with a single case study strategy. Data were collected through participatory observation, in-depth interviews with key informants (education directors, principals, teacher coordinators, and educators), and documentation studies. The validity of the data is guaranteed through the triangulation technique of sources and methods. Data analysis was carried out using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawing and verification. The results of the study show that curriculum management at SADIQ Maros is carried out in a collaborative, participatory, and adaptive manner. Curriculum planning integrates the Independent Curriculum with the philosophy of nature-based education and Islamic values, so that the curriculum becomes contextual and relevant to the needs of students and the surrounding environment. The organization of the curriculum is supported by a flexible and non-hierarchical structure, with teachers as the main actors in learning and the environment as the main learning space. The implementation of the curriculum emphasizes experiential learning, learning by doing, and contextual projects that encourage active involvement of students as well as strengthening character and ecological awareness. Curriculum evaluation is carried out in a continuous and holistic manner, not only assessing academic achievements, but also the development of students' character, life skills, and environmental concerns through authentic assessments and collaborative reflection. This study concludes that nature-based curriculum management at SADIQ Maros is able to create a dynamic, meaningful, and holistic learning ecosystem for student development. These findings provide a conceptual and practical contribution as a model for managing the natural school curriculum that is integrated with national education policies and relevant to be applied in efforts to improve the quality of continuing education.